Forest therapy using virtual reality in the older population: a systematic review - Clemente, Davide; Romano, Luciano; Zamboni, Elena; Carrus, Giuseppe; Panno, Angelo (Frontiers in Psychology, 2024)
As life expectancy increases, more attention needs to be paid to their mental and physical condition. Many older patients are also bedridden, which makes some treatments, like in vivo exposure to natural environments, more difficult to be applied. This study aimed to systematically review articles that include interventions combining virtual reality and forest environment, targeting a sample of older people. Based on PRISMA guidelines, we conducted a literature search in three databases (EBSCO, PubMed and Scopus), plus gray literature (OpenGrey). We considered only studies that used forest settings via virtual reality and included a sample with age≥ 65. After the screening and eligibility stages, 7 articles have been included. The study underlines the need to implement research in this direction to standardize effective procedures that can be used to improve the mental and physical health of the older people and caregivers, while also reducing social costs.